Directions for Improving Service Efficiency in Telecommunication Enterprises - Sadikmuratovich, Ibadullaev Sanjar (International Journal on Orange Technologies, 2023)
In order to understand the role of services provided by telecommunications operators, to determine the presence of innovative technologies and to identify problems that arise among subscribers, we conducted an anonymous sociological survey among the population, as well as to measure several We have developed a system of indicators. The results of a sociological survey prove once again that innovation and new technologies ensure customer loyalty. It can be concluded from the answers that the reforms carried out in different years: expansion of the network, import of new technologies and their introduction serve to form loyal customers. The only way to be competitive is to import innovative equipment, especially to provide new services by offering internet services at affordable prices to increase customer loyalty.